Esvaziamento gástrico e gastrinemia em gerbis infectados com cepas de Helicobacter pylori de diferentes expressões gênicas para o fragmento epyia - Carlyle Marques Barral (2013)
INTRODUCTION: Infection with Helicobacter pylori (HP) promotes gastric changes such as inflammation and changes in gastrointestinal hormones, which seem to be closely related to gastric motor disorders. It is possible that strains with different pathogenic profiles induce hormonal and motor response with different intensity. OBJECTIVES: This study aimed to evaluate the pattern of gastric emptying and serum gastrin of Mongolian gerbils (Meriones unguiculatus) infected with strains of HP with different patterns of pathogenicity. MATERIALS AND METHODS: A total of 56 Mongolian gerbils, females, four months old, and weighing 80.0 g were used. The animals were divided into four experimental groups: A (n = 8), control animals kept under observation for 180 days; B (n = 16), animals infected with standard strain CagA negative, consisting of eight animals (B1) studied for 45 days of infection and the remaining eight (B2) evaluated 180 days after infection; C (n = 16), animals infected with strain of HP with 1 epyia loci, consisting of eight animals (C1) studied 45 days after infection and the remaining eight (C2) after 180 days of infection; and D (n = 16), animals infected with CagA-positive strains and loci with 3 epyias, with eight animals evaluated 45 days after infection (D1) and eight animals studied 180 days after infection (D2). Gastric emptying was determined by a scintigraphic study performed in a Ventri gamma camera (GE-Healthcare Medical Systems, Milwaukee, EUA) after administration of a nutrient solution containing peptone broth 50% (Biobrás, Brazil) and 7.4 MBq of Phytate-99mTc. Microorganism presence in the gastric antrum was identified by polymerase chain reaction (PCR). The gastric antrum slides were evaluated for the degree of inflammation, with infiltration ranked as absent, mild, moderate, and severe. Serum gastrin was measured by enzyme immunoassay (ELISA). RESULTS: The PCR study was positive in all fragments from the antrum and body of infected animals (groups B, C, and D) and negative in non-infected animals (group A). The results showed greater inflammatory response in group D at 45 and 180 days of infection. There was an increase of the emptying rate in groups B and C, significant gastrin reduction in groups B and D, and increased hormone serum concentration in group C. CONCLUSIONS: Different strains of HP exhibited different patterns in gastrin secretion and gastric emptying, with CagA-negative strains and 1 epyia showing hypersecretory hormonal profile and hypermotility, and strains with 3 epyias with reduced secretion of gastrin and gastric hypomotility profile.